Sedimentation Rate Analysis in Public Port, Lhokseumawe City - Yudho Andika; Erniati; Imanullah; Hafli, T. Mudi; Hasibuan, Rani Adinda Melani; Harahap, Usnia Puada; Febriza, Fira; Putra, M. Afif Tri; Syakura, Abdan (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2025)
Sedimentation is the process of deposition of material from rocks that is transported by the movement of water and wind. Sedimentation that takes place continuously causes siltation in water areas. If shallowing occurs in the port area, it will have an impact on the decline in port functions and even threaten the security of sea transportation routes. The purpose of this study was to analyze the rate of sedimentation in the General Port of Lhokseumawe City which includes sediment characteristics and oceanographic parameters that affect the sedimentation process. This study used a survey method with purposive sampling at 4 observation stations for 7 days. The highest sedimentation rate was found at Station 4 which was 6,22 mg/cm2/day and the lowest at Station 2 which was 3,65 mg/cm2/day. The dominant sediment grain size in the General Port of Lhokseumawe City is very fine sand type with a value of 38,04%. PCA analysis of very fine sand type sediments deposited the most. The highest current velocity at station 2 with a value of 0.10 m/s while the highest tide on the first day was 320 cm in height. The current speed has an inversely correlation to the sedimentation rate with a value of 81,52%.